Wychowanie obywatelskie w jezuickich kolegiach szlacheckich... - Puchowski, Kazimierz (Horyzonty Wychowania, 2017)
In his article, K. Puchowski takes up the problem of civic education in Jesuit colleges for nobility in the First Republic of Poland. Establishing colleges was supposed to be the reaction of Jesuits, Piarists, and Theatines to the expectations of the state, which wanted to have well-prepared elites in order to introduce reforms necessary at that time. The author makes a brief comparison and analysis of the activity of colleges for nobility run by individual orders, with special attention paid to Jesuit colleges. Jesuit colleges in the Republic of Poland aimed at training exemplary citizens, full of religiousness and patriotism. The author disagrees with the standpoint, expressed in literature, that education in colleges for nobility was deprived of civic character, which he attempts to prove in the article, showing various forms and methods of shaping civic attitudes. Colleges passed on not only knowledge, but they also shaped the attitudes of respect for statehood. Jesuit schools were elitist, different from knights’ schools of the time. The teaching staff was well-prepared for conducting cultural and political education. They trained the sons of the well-known Polish noblemen cherishing hope that it would prove useful in the process of restoring the Republic of Poland. K. Puchowski enumerates the leading figures for the area under discussion, such as: Karol Wyrwicz, Franciszek Bohomolec, Adam Naruszewicz and others, who had influence on the shape of the colleges for nobility in the Crown and Lithuania. Those people were characterised by a critical approach towards what was happening in the Republic of Poland and willingness to educate enlightened citizens for the Homeland.